Impact of spirometry feedback and brief motivational counseling on long term smoking outcomes: A comparison of smokers with and without lung impairment - McClure, Jennifer B. (2010)
OBJECTIVE: We compared long-term outcomes among smokers with and without impaired lung functioning who received brief counseling highlighting their spirometric test results. METHODS: Participants in this analysis all received a brief motivational intervention for smoking cessation including spirometric testing and feedback (~20 minutes), were advised to quit smoking, offered free access to a phone-based smoking cessation program, and followed for one year. Outcomes were analyzed for smokers with (n = 99) and without (n = 168) impaired lung function. RESULTS: Participants with lung impairment reported greater use of self-help cessation materials at 6 months, greater use of non-study-provided counseling services at 6 and 12 months, higher 7-day PPA rates at 6 months, and were more likely to talk with their doctor about their spirometry results. CONCLUSION: Further research is warranted to determine if spirometry feedback has a differential treatment effect among smokers with and without lung impairment. PRACTICE IMPLICATIONS: It is premature to make practice recommendations based on these data.